The roles of angiopoietin-like 4 in cancer metastasis - Teo, Zi Qiang (2016)
Metastasis, the spread of cancer cells to distant tissues and/or organs, accounts for more than 90% of the mortality rate associated with cancer rate. Cancer metastasis is a complex, multistep event that began with the cancer cells undergoing EMT to gain motility and invasive capacity, leading to its invasion into the systemic circulation and subsequent dissemination to distal organs. Recently, tumor-secreted Angiopoietin-Iike 4 (ANGPTL4) was identified as a critical pro-metastatic gene in several cancers. However, the role of ANGPTL4 during metastasis is discordant due to the lack of mechanistic understanding. Our present work highlights dynamic roles of ANGPTL4 during malignant progression, particularly by coordinating EMT and the dissemination of metastatic cancer cells. We observed a striking correlation between ANGPTL4 expressions with tumor grades, suggesting that ANGPTL4 may have important roles during malignant progression. Indeed, we demonstrated that cancer cells are able to exploit ANGPTL4 at multiple stages of malignancy. We showed that cancer cells use ANGPTL4 to manipulate cancer cellular metabolic changes during EMT and synchronizes a metabolic shift necessary to drive EMT initiation through an ANGPTL4:14-3-3 signaling axis. Futhermore, we also demonstrated that tumor-derived ANGPTL4 behaves as a pro-vascular permeability factor where it mediates the vascular disruptive effect through a novel integrin a5pi-induced Rac/PAK signaling axis. These result in the declustering and internalization of endothelial cell-cell junctional proteins that disrupts the vascular integrity and enhances metastasis. Taken together, our findings revealed critical roles for ANGPTL4 during metastatic progression and provided new insights for therapeutic intervention against cancer metastasis.